Pengaruh Pertumbuhan Ekonomi dan Rata – Rata Lama Sekolah Terhadap Indeks Pembangunan Manusia di Kabupaten Banjar - Syairoji, Ahmad; Rusdiana, Rusdiana; Malihah, Lola (JURNAL LITBANG KOTA PEKALONGAN, 2024)
The Human Development Index is important parameter in describing development from human perspective based on three main dimensions, namely health, education and living standards. The ultimate goal of development should be to lead to better living conditions and of course prosperity and welfare of the people. Therefore, it is important to pay attention to existing human resources..This research aims to determine the influence of Economic Growth and Average Years o Schooling on the Human Development Index in Banjar Regency. This research uses a quantitative method with multiple linear regression analysis tools using secondary data obtained from BPS Banjar Regency for the period 2014-2023 which was processed using the SPSS 26 program calculation tool. The data collection technique is library study. Based on the results the simultaneous test, economic growth and the average length of schooling jointly influence the human development index in Banjar Regency, while the results of the partial test show that what influences the human development index is the variable average length of schooling and based on the Coefficient of Determination obtained of 0.966 or 96.6%. This means that 96.6% of the dependent variable, namely the human development index, can be explained or influenced by the independent variable.